Milk and dairy products as functional foods - Kanekanian, Ara (Chichester, West Sussex, UK ; Hoboken, NJ : John Wiley & Sons Inc., 2014)
"This book draws together a wealth of information regarding the functional health benefits of milk and dairy products"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Dairy products in human nutrition; Milk -- Analysis; Functional foods; TECHNOLOGY & ENGINEERING / Food Science; Dairy products in human nutrition; Functional foods; Milk -- Analysis; Dairy Products -- Analysis; Dairy products in human nutrition; Functional foods; Milk -- Analysis; Electronic books; Electronic books